Rancang Bangun Portal E-Commerce Semarang-Handycraft Berorientasi Obyek - Galih, Sinta Tridian; Mustafid, Mustafid; Sugiharto, Aris (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
Number of  emerging  Small  and  Medium  Enterprises  (SMEs)  in  Indonesia  has  not  been  matched  with  optimal  performance.  Manyproblems  arise  such  as  difficulty  in  marketing  products  and  limited  costs  for  marketing.  This  problem  can  be  overcome  by  utilizingInternet technology to build e-commerce portal. Portal help online marketing with no borders zone, facilitate for searching a consumer,can automate the promotion and business transactions that can help win the competition.In this research, to be built e -commerce portalSemarang-Handycraft. Design of e-commerce portal is using system development methodologies Model Driven Development (MDD)and UML modeling language (Unified Modeling Language) which is a visual language for modeling object -oriented language and byusing the  Open Source  Content Management  Systems  that  is  called  Joomla  and  using  e-commerce  modules Virtuemart.  Produced  ecommerce portal that can provide information with better quality and can be accessed at http://semarang-handycraft.cz.cc, which is a newalternative  for  the  production  of  marketing  handicraft  products  of  SMEs  in  Semarang.  For  security  and  convinience  of   informationretrieval in e-commerce portal is divided into several access rights, ie rights of access to regular visitors, members and administratorsKeywords: E-commerce; Portals; UML; Object-oriented